Cranberry – A Boon in Periodontal Therapy - Prachi Khuntia,1 Rashmita Nayak2, Abhaya Chandra Das3, Rinkee Mohanty4 , Saurav Panda3 ,Sharmistha D (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cranberry juice has been used in medical fields for the past decade because of its several health benefits.Due to its properties, cranberries and its molecular components have gained attention by the researchers.The chief bioactive component of cranberry is proanthocyanidins. Its improved health benefits are alreadybeing found in treating UTI and many systemic diseases. But only a few studies have shown its effect onoral health.